The Historical Connection Between Short Term Output and Prices in a Small Open Economy - Ola Honningdal Grytten; Arngrim Hunnes (Norges Bank, 2009)
According to a Keynesian view, short term output fluctuations are normally demand side led. Since prices reflect demand, they should mirror output fluctuations. Thus, prices and output are expected to move in the same direction in the short run. The present paper investigates the historical co-movements of output and prices for a small open raw material based economy, in this case Norway 1830-2006. We find little evidence of a positive relationship. On the contrary, we rather find negative correlations between the two variables, indicating that supply side shocks through the foreign sector were more important for historical business cycles in Norway than assumed hitherto.
hdl:11250/2497620
Keywords: E31; E32; N10; N13; N14; 330; business cycles; output; small open economy; price fluctuations